2010
DOI: 10.1089/dna.2009.0997
|View full text |Cite
|
Sign up to set email alerts
|

Age- and Diet-Specific Effects of Variation atS6 Kinaseon Life History, Metabolic, and Immune Response Traits inDrosophila melanogaster

Abstract: Life history theory hypothesizes that genetically based variation in life history traits results from alleles that alter age-specific patterns of energy allocation among the competing demands of reproduction, storage, and maintenance. Despite the important role that alleles with age-specific effects must play in life history evolution, few naturally occurring alleles with age-specific effects on life history traits have been identified. A recent mapping study identified S6 kinase (S6k) as a candidate gene affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 62 publications
(57 reference statements)
2
9
0
Order By: Relevance
“…Here we show that AccS6K-p70 plays an important role in multiple developmental processes in A. c. cerana. First of all, expression amount of AccS6K-p70 varied in different developmental stages, which is consistent with other research results that show that the effect of S6K in D. melanogaster is age specific (Cho et al, 2010). In comparison to pupae, the expression level of AccS6K-p70 in the Chinese honeybee is relatively high in larvae and adults.…”
Section: Discussionsupporting
confidence: 90%
“…Here we show that AccS6K-p70 plays an important role in multiple developmental processes in A. c. cerana. First of all, expression amount of AccS6K-p70 varied in different developmental stages, which is consistent with other research results that show that the effect of S6K in D. melanogaster is age specific (Cho et al, 2010). In comparison to pupae, the expression level of AccS6K-p70 in the Chinese honeybee is relatively high in larvae and adults.…”
Section: Discussionsupporting
confidence: 90%
“…Evidence to suggest that the genetic basis of variation in complex traits changes with age has been provided at the levels of QTL 19,30 , genes 25,31 and transcripts 26 ; however, our work is the first to provide evidence of this at the SNP level. If this is the general case, it suggests that greater insight into the genetic architecture of phenotypic variation will be provided by mapping genotype to phenotype in an age-specific manner.…”
Section: Nature Communications | Doi: 101038/ncomms5338mentioning
confidence: 76%
“…Recent work has suggested that the genetic basis of complex traits changes with age 19,25,26 , but this age-specific pattern has not yet been demonstrated at the level of individual single-nucleotide polymorphisms (SNPs).…”
mentioning
confidence: 99%
“…Activation of the TOR pathway results in the phosphorylation of S6K, which mediates protein synthesis, cell growth, and other cellular processes (Miron and Sonenberg 2001;Ma and Blenis 2009;Katewa and Kapahi 2011). Earlier work in our lab found that a hypomorphic mutation in S6k, a gene acting downstream of TOR, resulted in decreased bacterial ability to clear infection by E. coli (Cho et al 2010). Therefore, it is possible that bacterial clearance is mediated by activation of TOR signaling by higher mos levels.…”
Section: Discussionmentioning
confidence: 92%
“…The idea that alleles with age-specific effects contribute to the natural variation and evolution of senescence is a fundamental assumption of life-history theory and evolutionary theories of aging. Nevertheless, the age-specific effects of natural alleles on phenotypes are rarely studied (Hughes 2010; but see Cho et al 2010). As a result, we know little about how common these effects are, how they are regulated at the genetic level, or what genes or pathways produce age-related phenotypic changes.…”
mentioning
confidence: 99%